Unexpected outcomes from an AI education course among education faculty: Toward making AI accessible with marginalized youth in urban Mexico - Kasun, G. Sue; Liao, Yin-Chan; Margulieux, Lauren Elizabeth; Woodall, Maya (Frontiers in Education, 2024)
This community case study foregrounds an AI access project completed by education faculty who took a course on AI and education together in 2023. It centers a teacher education faculty's work when she presented the final project, a workshop with marginalized urban youth in Mexico about what AI is. It shows how teacher education faculty can migrate to digital learning, and especially AI, while also speaking to the importance of providing access to and with the Global South as a question of equity.